Why do consumers buy recycled shoes? An amalgamation of the theory of reasoned action and the theory of planned behaviour - Yadav, Sher Singh; Kar, Sanjay Kumar; Rai, Prashant Kumar (Frontiers in Environmental Science, 2022)
The footwear industry’s transition to a circular economy is a essential for sustainable development. The emerging recycled shoe production may lead to sustainable consumption in the footwear industry. Consumers are now more cognizant of the negative effects of their shopping choices. We studied the factors influencing consumers’ intentions of buying recycled shoes. We applied the theory of reasoned action (TRA) and the theory of planned behaviour (TPB). As this is an emerging trend, there is a dearth of sufficient literature regarding sustainable recycled shoe purchase behaviour. We aimed to fill this broad gap with this empirical research. We found that perceived environmental knowledge, subjective norms, sustainable label awareness, and shoe choice motives influenced attitude, and attitude, word of mouth, and environmental consciousness shaped purchase intentions. Sustainable label awareness, shoe surplus, and purchase intentions affected purchase behaviour. The study is beneficial for policymakers and managers of companies for making decisions related to footwear product positioning and targeting.